2019
DOI: 10.3390/polym11040614
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Resorcinol-Based Phosphazene-Containing Epoxy Oligomers

Abstract: Phosphazene-containing epoxy-resorcinol oligomers (PERO) are synthesized in one stage with the direct interaction of hexachlorocyclotriphosphazene (HCP), resorcinol, and epichlorohydrin in the presence of solid NaOH. Depending on the initial ratio of HCP:resorcinol, PERO contains from 20 to 50 wt.% phosphazene component (2.0–4.8% of phosphorus) and have an epoxy group content up to 30 %. Products are characterized using 1H and 31P NMR spectroscopy, MALDI-TOF mass spectrometry, and elemental analysis. According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…It can be explained by bisphenol A and resorcinol spacers in the structure of P‐bapp and P‐tper correspondingly. For example, resorcinol‐based epoxy oligomers are known to have lower viscosity compared to bisphenol A‐based epoxides 48 . Similarly, P‐tper monomer has about five times lower viscosity compared to P‐bapp monomer.…”
Section: Resultsmentioning
confidence: 99%
“…It can be explained by bisphenol A and resorcinol spacers in the structure of P‐bapp and P‐tper correspondingly. For example, resorcinol‐based epoxy oligomers are known to have lower viscosity compared to bisphenol A‐based epoxides 48 . Similarly, P‐tper monomer has about five times lower viscosity compared to P‐bapp monomer.…”
Section: Resultsmentioning
confidence: 99%
“…The other example is hexaphenoxycyclotriphosphazene, which is used as a highly effective flame retardant for a large number of synthetic polymers. A number of effective flame-retarded functional epoxy resins, amine curing agents and benzoxazines with a phosphazene core have been proposed [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Carboxyl-containing epoxyphosphazenes and their use as a catalyst for the polymerization of benzoxazines have also been reported [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of product, whether resins, flame retardants or curing agents that can be easily obtained on the basis of universal halophosphazenes, are responsible for the undying interest of researchers in phosphazenes [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Arylphosphazenes compared with other organophosphorus compounds, have, as a rule, higher thermal stability and chemical resistance and are promising fire retardants [ 4 , 6 , 13 , 14 ], characterized by the synergistic effect of phosphorus and nitrogen [ 15 ]. Thus, phenoxycyclophosphazenes were commercialized as a flame retardant by Otsuka Chemical et al Recently it was shown that epoxy-amine matrices modified with epoxycyclophosphazene [ 16 ] are characterized by enhanced mechanical properties [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, epoxy resins modified with epoxycyclophosphazenes appear to be a promising base for halogen-free binders for critical use. Recently, scalable methods for epoxycyclophosphazene synthesis have appeared [ 6 , 16 , 18 ], which make it possible to believe that they may become available starting components in the market for composite manufacture.…”
Section: Introductionmentioning
confidence: 99%